INSTITUTE OF HISTOLOGY AND EMBRYOLOGY "PROF. DR ALEKSANDAR Đ. KOSTIĆ” THROUGH THE PRISM OF ITS FOUNDER’S FATE - MARKING THE 100th ANNIVERSARY OF THE INSTITUTE - Puskas, Nela (HEALTH CARE, 2021)
Institute of Histology and Embryology "Prof. Dr. Aleksandar Đ. Kostić" this year celebrates one century since it has been established. The founder of the Institute, the first professor of histology and embryology and the first director of the Institute was Prof. Dr. Aleksandar Kostić, one of the last Renaissance figures of the XX century. With great effort, commitment and enthusiasm, from the room where nothing but the walls, floor, and ceiling were, he built the Institute as the most modern building in Southeast Europe, which had, at that time, extremely high quality conditions for teaching, extremely dedicated staff but also highly developed research, library, terminology, photo-film activity. After the bombing of Belgrade and the Institute building, he once again raised and set up the Institute during his lifetime, and then, due to ideological disagreements, was retired and removed from the faculty by force of law.  Because he experienced many injustices, all with an ideological background, until the end of his life he lived a life with incurable pain in his soul. He was rehabilitated posthumously in 2001.
Keywords: history, Institute of Histology and Embryology, Professor Aleksandar Đ. Kostić